Perceptions of Transferrable Skills of Chemistry Teacher Candidates in the Utilization of Learning ICT - Ratna Unaida; Isna Rezkia Lukman; Fakhrah (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Transferable skills are the core competencies needed to apply basic skills and problem-solving skills to make the environment one of the main elements of education policy. This research was conducted at the Chemistry Education Study Program, at Malikussaleh University in September and November 2022. This research aims to: Know the perceptions of prospective teachers regarding the transferable skills they have in utilizing ICT for learning. This type of research is qualitative descriptive research. The subjects of this research are students in the Chemistry Education Study Program with the object of research namely Perception of Transferable skills. The data collection techniques used are questionnaires and interviews in utilizing ICT learning based on aspects of transferable skills. The data analysis carried out for this study was to process and describe data with descriptive statistics. Measuring the score of the questionnaire data results is calculated using a Likert scale measurement scale. The results obtained from this study, namely students' perceptions of their transferable skills indicate that the perceptions of prospective teachers are more prominent in the aspects of collaboration and communicating with students. As for the characteristics of mastering digital literacy, future teachers still feel that they are not optimal in utilizing digital technology, which is now widespread and widespread in the world of education.